Influence of ingesting casein protein and whey protein carbohydrate beverages on recovery and performance of an endurance cycling test - Cepero, M.; Padial, R.; Rojas, F. J.; Geerlings, A.; de la Cruz, J. C.; Boza, J. J. (Journal of Human Sport & Exercise, 2010)
The main aim of this study was to determine if short-term post exercise recovery, cycling performance and blood analysis were altered when consuming three different beverages with the same amounts of calories, a carbohydrate-only beverage (CHO, 9% carbohydrate) a carbohydrate and casein protein beverage (CHO+Pc, 7% carbohydrate and 2% protein) and a carbohydrate and whey hydrolyzed drink (CHO+Pw, 7% + 2 %). Fifteen male cyclists (VO2peak= 63.4±9.6 ml·kg-1·min-1) performed three trials using a randomly counterbalanced, double-blind design. In each trial one litre of one of the test drinks was consumed in fasting conditions after 1 hour ride at 75% VO2peak. After a two hours recovery period the cyclists rode 20 km at the rider's maximum speed for this distance. The results showed no significant differences in the 20-km ride when consuming the CHO (1770±210 s), the CHO+Pc drink (1819±185 s) or the CHO+Pw (1803±201). Post-exercise creatine kinase (CK) was not significantly different between treatments. However, serum insulin concentrations were higher during recovery when CHO+Pc and CHO+Pw beverages were consumed